Diagnostic and Epitope Mapping Potential of Single-Chain Antibody Fragments Against Foot-and-Mouth Disease Virus Serotypes A, SAT1, and SAT3 - Chitray, Melanie; Opperman, Pamela Anne; Rotherham, Lia; Fehrsen, Jeanni; van Wyngaardt, Wouter; Frischmuth, Janine; Rieder, Elizabeth; Maree, Francois Frederick (Frontiers in Veterinary Science, 2020)
Foot-and-mouth disease (FMD) affects cloven-hoofed domestic and wildlife animals and an outbreak can cause severe losses in milk production, reduction in meat production and death amongst young animals. Several parts of Asia, most of Africa, and the Middle East remain endemic, thus emphasis on improved FMD vaccines, diagnostic assays, and control measures are key research areas. FMD virus (FMDV) populations are quasispecies, which pose serious implications in vaccine design and efficacy where an effective vaccine should include multiple independent neutralizing epitopes to elicit an adequate immune response. Further investigation of the residues that comprise the antigenic determinants of the virus will allow the identification of mutations in outbreak strains that potentially lessen the efficacy of a vaccine. Additionally, of utmost importance in endemic regions, is the accurate diagnosis of FMDV infection for the control and eradication of the disease. To this end, a phage display library was explored to identify FMDV epitopes for recombinant vaccines and for the generation of reagents for improved diagnostic FMD enzyme-linked immunosorbent assays (ELISAs). A naïve semi-synthetic chicken single chain variable fragment (scFv) phage display library i.e., the Nkuku® library was used for bio-panning against FMD Southern-African Territories (SAT) 1, SAT3, and serotype A viruses. Biopanning yielded one unique scFv against SAT1, two for SAT3, and nine for A22. SAT1 and SAT3 specific scFvs were exploited as capturing and detecting reagents to develop an improved diagnostic ELISA for FMDV. The SAT1 soluble scFv showed potential as a detecting reagent in the liquid phase blocking ELISA (LPBE) as it reacted specifically with a panel of SAT1 viruses, albeit with different ELISA absorbance signals. The SAT1svFv1 had little or no change on its paratope when coated on polystyrene plates whilst the SAT3scFv's paratope may have changed. SAT1 and SAT3 soluble scFvs did not neutralize the SAT1 and SAT3 viruses; however, three of the nine A22 binders i.e., A22scFv1, A22scFv2, and A22scFv8 were able to neutralize A22 virus. Following the generation of virus escape mutants through successive virus passage under scFv pressure, FMDV epitopes were postulated i.e., RGD+3 and +4 positions respectively, proving the epitope mapping potential of scFvs.